Efektivitas Pupuk Organik dan Anorganik pada Pertumbuhan dan Hasil Brokoli (Brassica oleracea var. italica) - Lilik Tri Indriyati (Institut Pertanian Bogor, 2018)
Broccoli (Brassica oleracea var. italica) is one of exotic vegetables having a high value, highly nutritious, rich source of vitamins, and also it contains the glucoraphanin compound which have anticancerous properties. Integrated nutrient management between organic and inorganic fertilizers is an important demand of the present era to increase broccoli yield and to cultivate a land in such a way that the soil productivity should remain sustainable. This research was conducted to study the effectiveness of organic and inorganic fertilizers on the growth and yield of broccoli. There were eight treatments which consisted of organic and inorganic fertilizers with different applications, single or in combination, and control (without fertilizer). Plant of broccoli as an indicator plant was measured for its height and number of leaves for variables of plant growth parameter, and head weight and head diameter for variables of yield. Application of organic and/or inorganic fertilizers significantly increased the growth of broccoli plant compared with control, but they did not show a significant difference with standard NPK treatment. Combination of organic fertilizer at a rate of 4 tons ha-1 and 50% the standard NPK fertilizer showed the highest diameter and yield of broccoli head. The sole application of organic fertilizer at a rate of 4 tons/ha showed the similargrowth and yield of broccoli with standard NPK treatment.